COMMON PROBLEMS FACED BY FOREIGN LANGUAGE LEARNERS - Olimova Nodira Oybekovna (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2020)
Learning foreign language as a second language is not really easy. If you are learning language outside of the country which learning language is spoken, certainly you encounter certain kind of problems. These problems can make some obstacles to grasp new language although the learner are willing to learn new language. The problems can be considered as challenges because of the strong interest. However, how can these problems can be solved? To answer this question scholars specified main dilemmas and tried to explained about the causes.